Subarachnoid Hemorrhage from Brain Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Six children with subarachnoid hemorrhage as the initial symptom of brain tumor are reported from the Depts of Neurosurgery, Univ.